FAKTOR DETERMINAN PERUBAHAN PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN SUMBAWA - Meri Ardianti; Rosyidah Rachman; Abdul Rahim (Pusat Riset dan Publikasi, 2023)
This study aims to know the effect of regional taxes and retribution on changes the Local Generated Revenue (PAD) in Sumbawa District. The type of this study was associative study. The type of data used is quantitative data obtained from secondary sources. The method used to collect data used was through documentation study. The data analysis tool used was multiple linear regression, partial parameter hypothesis test (t test), simultaneous parameter hypothesis test (F test), and the coefficient of determination test (R2). The results of study showed that the Regional taxes and regional levies have a positive and significant effect on changes the Local Generated Revenue (PAD) in Sumbawa Regency in 2017-2021, both partially and simultaneously. The ability of regional tax and regional levies variables to influence changes the Local Generated Revenue (PAD) in Sumbawa Regency in 2017-2021 is 41%, while the remaining 59% is influenced by other variables outside this research model.